Improving English Vocabulary Mastery through Audio Lingual and Drill Methods for Class VII-I in English Subjects at MTs “Wali Songo” Ngabar Ponorogo - Fidella Alivia Wahyuning Arief; Imam Rohani (Tarbawi: Journal of Islamic Education, 2022)
This study was structured with the aim of knowing the effectiveness of the Audio Lingual and Drill learning method in improving vocabulary mastery of the VII-I grade students of MTs "Wali Songo" Ngabar Ponorogo. The subjects of this study were students of class VII-I, totaling 25 female students. This research is an action research classroom and was conducted in two cycles. Each cycle is carried out with the stages of planning, implementing, observing, and reflecting. This research was conducted in the even semester of the 2021/2022 academic year, namely in December. Data were analyzed descriptively and presented in the form of tables and graphs. The results showed an increase in students' vocabulary mastery in English, namely in the first cycle by 64% then in the second cycle, it increased to 80%. It is said that there is an increase of 16%, with the use of the Audio Lingual and Drill method in English subjects can improve the understanding and mastery of words of students in grades VII-I MTs “Wali Songo” Ngabar Ponorogo.